2005
DOI: 10.1017/s0033291705005416
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of attempted suicides seen in emergency-care settings of general hospitals in eight low- and middle-income countries

Abstract: Action for the prevention of suicide attempts can be started immediately in the sites investigated by addressing the one most important method of attempted suicide, namely self-poisoning. Regulations for the access to drugs, medicaments, pesticides, and other toxic substances need to be improved and revised regulations must be implemented by integrating the efforts of different sectors, such as health, agriculture, education, and justice. The care of patients who attempt suicide needs to include routine psychi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
94
5
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(121 citation statements)
references
References 14 publications
13
94
5
7
Order By: Relevance
“…The finding consistent with the literature is that most of the cases reported represented persons in the age range 20-35 years (67.7%) [11] followed by 13-19 years (19.1%). This supports research that indicates that adolescents and young people are most at risk for suicide attempts [6,7,9]. Moreover, all other age categories showed high self-poisoning tendency in male except in 13-19 age category where female reported nearly twice admissions due to self-harm (Tables 1 and 2).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The finding consistent with the literature is that most of the cases reported represented persons in the age range 20-35 years (67.7%) [11] followed by 13-19 years (19.1%). This supports research that indicates that adolescents and young people are most at risk for suicide attempts [6,7,9]. Moreover, all other age categories showed high self-poisoning tendency in male except in 13-19 age category where female reported nearly twice admissions due to self-harm (Tables 1 and 2).…”
Section: Resultssupporting
confidence: 87%
“…The results from this study revealed that most of the cases reported to the emergency department for suicide attempt by self-poisoning were males, a finding that is contrary to the previous studies where female outnumbered male [6][7][8][9][10]. The male:female ratio was 1:0.86 and significant (p<0.01).…”
Section: Resultscontrasting
confidence: 84%
See 1 more Smart Citation
“…These findings are in agreement with the literature 5,13,21,30 . With regard to these differences, the literature emphasizes that men use more deadly methods and, for this reason, are more successful in their suicide attempts.…”
Section: * áLcool E Gás Sinais Convencionais Utilizados: Dado Numérisupporting
confidence: 94%
“…Um estudo realizado em salas de emergência de 8 países de baixa/mé-dia renda mostrou que, em metade dos serviços de emergência estudados, menos de um terço dos pacientes admitidos por tentativa de suicídio foi encaminhada para posterior avaliação e acompanhamento em serviços de saúde. 10 Até recentemente, o suicídio não era encarado como um problema de saúde pública no Brasil, provavelmente obscurecido pelas altas taxas de mortalidade por homicídio e acidentes de trânsito que ainda vigoram no país. No entanto, de 1998 a 2008, houve um aumento de 33,5% no número total de mortes por suicídio no Brasil, 11 o que reforça a necessidade de políticas públicas para a prevenção de mortes por suicídio.…”
Section: Avaliação De Risco Suicidaunclassified